Matching of O2 Utilization and O2 Delivery in Contracting Skeletal Muscle in Health, Aging, and Heart Failure - Nyberg, Michael; Jones, Andrew M. (Frontiers in Physiology, 2022)
Skeletal muscle is one of the most dynamic metabolic organs as evidenced by increases in metabolic rate of >150-fold from rest to maximal contractile activity. Because of limited intracellular stores of ATP, activation of metabolic pathways is required to maintain the necessary rates of ATP re-synthesis during sustained contractions. During the very early phase, phosphocreatine hydrolysis and anaerobic glycolysis prevails but as activity extends beyond ∼1 min, oxidative phosphorylation becomes the major ATP-generating pathway. Oxidative metabolism of macronutrients is highly dependent on the cardiovascular system to deliver O2 to the contracting muscle fibres, which is ensured through a tight coupling between skeletal muscle O2 utilization and O2 delivery. However, to what extent O2 delivery is ideal in terms of enabling optimal metabolic and contractile function is context-dependent and determined by a complex interaction of several regulatory systems. The first part of the review focuses on local and systemic mechanisms involved in the regulation of O2 delivery and how integration of these influences the matching of skeletal muscle O2 demand and O2 delivery. In the second part, alterations in cardiovascular function and structure associated with aging and heart failure, and how these impact metabolic and contractile function, will be addressed. Where applicable, the potential of exercise training to offset/reverse age- and disease-related cardiovascular declines will be highlighted in the context of skeletal muscle metabolic function. The review focuses on human data but also covers animal observations.